Transferring and sustaining technological innovations after professional development: Insights from school leaders and teachers in Sub-Saharan Africa (Journal of Applied Learning and Teaching, 2022)
Desiring technology-related change promotes reform-oriented technology integration to create a lasting impact on education. Nonetheless, most technology projects in Sub-Saharan Africa least achieved this target. Research points to quality professional development (PD) as a significant influence in achieving this. This follow-up study is on a cohort of 6,351 school leaders and teachers from six Sub-Saharan African countries who participated in a digital instructional PD targeted at building their capacity to embed ICT into school organisation and curriculum practices. The study sought to evaluate the impact of the PD programme in relation to the quality and the extent of the participants’ transfer of the programme’s ideas from capacity building to school organisation and classroom practices. A semi-structured survey instrument and diaries, kept to maintain records of activities and events during the period of implementation, were data channels. Findings revealed that stakeholder groups expressed general satisfaction with content and processes of the training programme; however, essential conditions to support transfer of the training’s ideas to school level seemed inadequate during the period of implementation. Implications of the study for effective technology-related PD that have sustainable impact on educational practices particularly in Sub-Saharan regions and similar contexts are discussed in this article.